Application of Mobile Interactive Applications in College English Teaching from the Perspective of Intelligent Educational Technology - Zhao, Ran (International Journal of Interactive Mobile Technologies (iJIM), 2025)
In the context of the challenges posed by personalization and effectiveness in college English teaching, the deep integration of intelligent educational technology and mobile learning has become a key solution. This paper aims to explore how advanced algorithms can be applied to mobile interactive applications to create an intelligent and immersive college English teaching environment. The study first designs an “Artificial intelligence (AI)-immersive task-based dialogue laboratory” as the core application scenario, where students engage in language learning by completing communication tasks in highly realistic virtual environments. To achieve natural interaction and precise feedback, this paper focuses on the development of two core technologies: First, a new continuous speech control method is proposed, optimizing matching efficiency and robustness through windowing limitations and weighting strategies, ensuring accurate understanding of students’ natural spoken commands and smooth scene navigation. Second, a pronunciation quality evaluation system is constructed by integrating multiple speech features and adopting a multi-task learning framework, allowing for real-time, finegrained diagnostics and feedback on pronunciation at the phoneme, word, and sentence levels. The study ultimately demonstrates that technology integration driven by educational scenarios can significantly enhance the interactive experience and teaching efficiency in college English learning, providing a practical solution for intelligent foreign language teaching.